Penerapan dan Pemantauan Pakan Ikan Lele Otomatis Menggunakan Keypad Shield Berbasis IoT - Muhamad Ariandi; Imam Karua (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2023)
Cultivating freshwater fish is a promising business in the long term. One type of freshwater fish that is widely cultivated by people is catfish. Catfish is a type of freshwater fish that does not require a lot of care, so it is very profitable and has high economic value. The problem that often occurs in catfish farming is that when feeding fish, farmers are often late in providing fish food, which causes catfish to die and experience cannibalism or eat other species. Based on the problems that occurred, research was carried out at Agrowisata Tekno 44 which aimed to implement an automatic catfish feeding device through the Internet of Things (IoT) based Blynk system which can be controlled using an LCD Keypad Shield which can provide a warning if the feed approaches a predetermined minimum limit. Addition of Mega+Wifi R3 Atmega 2560+ESP 8266 which functions as a link between the automatic fish feed and the Blynk application. The research method used in writing this article is a literature study by comparing the results of ultrasonic sensor measurements with a measuring tool in the form of a vernier caliper, and an interview method with cultivators to obtain information about feeding. Scheduled measurements at a specified time to obtain maximum results, an ultrasonic sensor was added to the fish feed container which functions to determine the contents of the volume of the RTC fish feed container which is used to store time information from the automatic fish feed tool, Push Button to measure the amount feed, the servo motor is used to open and close the fish food container that will exit into the fish pond. Testing the ultrasonic sensor with a vernier caliper to measure the distance that detects fish food in the fish food container produces a measurement ratio with a difference of 0.1 from the comparison between the measurements of the ultrasonic sensor and the vernier caliper. The results of testing carried out for 7 days with automatic fish feeding running according to a predetermined schedule, namely 06.00 and 18.00 with a success rate of 100% accuracy. And the success of the feed weight was 95.6% with an average accuracy of 96%, meaning that the fish did not lack food due to the lack of feed received.